2015
DOI: 10.1002/brb3.354
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of chemotherapy‐induced peripheral neuropathy using the LDIFLARE technique: a novel technique to detect neural small fiber dysfunction

Abstract: IntroductionThe diagnosis and quantification of chemotherapy-induced peripheral neuropathy (CIPN) remains a challenge. Conventional methods including quantitative sensory testing (QST), nerve conduction tests, and biopsy are unable to detect subclinical changes, and do not consistently correlate with severity of patients' symptoms and functional impairment. This study aims to determine the utility of the LDI (laser Doppler imager) FLARE technique in the diagnosis of CIPN and whether it correlates with symptom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 33 publications
3
30
0
Order By: Relevance
“…In several conditions – diabetes (Sumner et al, ; Said, ) , chemotherapy‐induced neuropathy (Sharma et al, ) , Sjögren's syndrome (Chai et al, ) , amyloidosis (Marian et al, ) and alcohol‐related neuropathy (Zambelis et al, ) – evidence suggests that small nerve fibers are among the earliest to be involved in peripheral neuropathy. Neuropathy is expected to affect the sudomotor C fibers, which innervate SGs, in parallel with other nerve fiber types, especially small unmyelinated fibers.…”
Section: Introductionmentioning
confidence: 99%
“…In several conditions – diabetes (Sumner et al, ; Said, ) , chemotherapy‐induced neuropathy (Sharma et al, ) , Sjögren's syndrome (Chai et al, ) , amyloidosis (Marian et al, ) and alcohol‐related neuropathy (Zambelis et al, ) – evidence suggests that small nerve fibers are among the earliest to be involved in peripheral neuropathy. Neuropathy is expected to affect the sudomotor C fibers, which innervate SGs, in parallel with other nerve fiber types, especially small unmyelinated fibers.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study failed to establish the utility of this POCD in a similar patient group: neither SNAP nor SNCV differed significantly between 24 patients with CIPN and 24 age‐matched healthy volunteers . Moreover, SNAP and SNCV did not correlate with the severity of CIPN.…”
Section: Discussionmentioning
confidence: 80%
“…Laser Doppler Imager Flare technique correlated well with EORTC QLQ-CIPN20 scores (Sharma et al, 2015) and Vibratron II correlated well with the cumulative chemotherapy dose (Chaudhry et al, 1994).…”
Section: Discussionmentioning
confidence: 81%
“…PainVision measures were associated with the onset of neuropathic symptoms (Sato et al., 2017) and correlated significantly with NCI‐CTCAE grades in patients receiving paclitaxel (Tanabe et al., 2013); however, it showed no significant correlation with visual analogue scale scores when used for assessment of OXLIPN (Yoshida et al., 2015). In patients on platinum‐ or taxane‐based regimens, Laser Doppler Imager Flare technique correlated well with EORTC QLQ‐CIPN20 scores (Sharma et al., 2015) and Vibratron II correlated well with the cumulative chemotherapy dose (Chaudhry et al., 1994). Another study suggested that Sudoscan, a device that measures electrochemical skin conductance, could be used to screen and follow CIPN (Saad et al., 2016).…”
Section: Discussionmentioning
confidence: 94%